Kolokwium patrystyczno-archeologiczne w Lublinie - Malinowski, Andrzej (Vox Patrum, 1981)
Report from the scientific symposium organized by the Inter-Faculty Department of Christian Antiquity Research at the Catholic University of Lublin on March 11-12, 1981.